Characterization and stabilization of tropical lowland peats in Banting area, Selangor, Malaysia / Azlan Shah Nerwan Shah @ Nintin - Azlan Shah, Nerwan Shah @ Nintin (2019)
Peat soil is a representative material of soil and well known as rich in organic matters, high compressibility, high porosity and low shear strength. During the dry seasons, peat lands will loss a lot of water and potentially turn into a tinderbox bringing in fires. When peat forest fire happens, it causes degradation of humic-rich organic matter eventually reduce the stability of peat soil. The impacts of peat fire on peat soil from degraded area in Banting, Selangor Peninsular Malaysia were investigated through the field identification, physico-chemical and engineering properties through burnt peat site. The field identification of peat were assigned based on the Von Post degree of Humification (H1 to H10) namely peat decomposition level based on the proportion of matter that had lost its cellular structure due to the decomposition of plant residues. The physical properties of the peat samples were determined through natural moisture content (NMC), organic content (OC), ash content and pH value. The engineering properties of peat was determined by shrinkage limit (Ls) of untreated and stabilised peat and unconfined compressive strength (UCS) test to determine the strength gain after 14 and 28 days of curing period. Based on field identification, peat soil is composed of slightly to highly decomposed peat ranging from H3 to H9 according to Von Post Degree of Humification Scale whereas the fibrous content of peat is proportionally increase with depth thickness of peat basin. The peat in study area generally can be categorized as fibric, fibric to hemic, hemic, hemic to sapric and sapric texture with presence of burnt peat layer at top of the peat basin. The result of Radiocarbon Dating (14C) Analysis also shown an age of peat significantly increase within the depthness of basin. The UCS result shows the burnt peat soil gained in strength that strongly related to the physico-chemical properties, degree of humification, binder and filler dosage and curing time. The most important geotechnical aspects of peat that have effect on stabilization process are natural water content, humification grade, ash content and pH value. The strength of burnt peat can be considerably improved by stabilization and support the concept of Air Curing Technique. The value of UCS strength increased with the gain of moisture content of peat samples but the strength tend to decrease when the moisture content exceeds certain point. The organic material changed its physical and chemical structure resulting from the fire event, thus the capability of the soil to hold water particles is reduce and yielded higher UCS strength of cement-peat-stabilization. The results also suggested that lateral variation within the peat basin indirectly affects the strength of cement-peat-stabilization.